Concrete performance evaluation of coarse aggregate replacement by civil construction waste - Oliveira, Juliane Patricia; dos Santos, Carlos Henrique; Okumura, Maria Lúcia; Ueda Yamaguchi, Natália (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The construction sector is considered a major generator of environmental impacts due to the high consumption of natural resources and waste generation. Thus, this article aims to evaluate the performance of a concrete produced by the partial and total replacement of natural coarse aggregate by recycled coarse aggregate, derived from the concrete residue of buildings and demolitions. The study was made by comparing the compressive strength and absorption of three different concrete traces, keeping the water/cement factor of 0.60 and changing only the proportions of recycled coarse aggregate between 0%, 50% and 100%. The results showed that the higher the percentage of substitution, the greater the water absorption and the lower the resistance results concrete compression. This result was obtained due to the lighter characteristic of the recycled aggregate compared to the natural aggregate. It was concluded that the concrete produced with recycled aggregates could be used in nonstructural functions, giving an adequate destination to the construction and demolition waste and consequently reducing the extraction and consumption of natural resources and contributing for the sustainable development.